2021
DOI: 10.3390/geriatrics6030085
|View full text |Cite
|
Sign up to set email alerts
|

SART and Individual Trial Mistake Thresholds: Predictive Model for Mobility Decline

Abstract: The Sustained Attention to Response Task (SART) has been used to measure neurocognitive functions in older adults. However, simplified average features of this complex dataset may result in loss of primary information and fail to express associations between test performance and clinically meaningful outcomes. Here, we describe a new method to visualise individual trial (raw) information obtained from the SART test, vis-à-vis age, and groups based on mobility status in a large population-based study of ageing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 68 publications
0
32
0
Order By: Relevance
“…In order to assess global cognitive status, frequently used tests are the Mini-Mental State Examination (MMSE) score as a standard measure of overall cognitive status [ 35 ], and the Montreal Cognitive Assessment (MoCA) [ 36 ], a more challenging cognitive test compared to the MMSE, which includes executive function, higher-level language, and complex visuospatial processing, and is designed to detect milder impairments. In our previous investigation, we did not find a significant association between baseline SART performance and cognitive decline at 4 years as assessed by MMSE score [ 7 ], although SART performance and MMSE score offer two different measures of the same physiological system. Therefore, it was necessary to employ a different technique, which could allow to a higher specificity and detection of a small number of participants with signs of both physical and cognitive decline.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…In order to assess global cognitive status, frequently used tests are the Mini-Mental State Examination (MMSE) score as a standard measure of overall cognitive status [ 35 ], and the Montreal Cognitive Assessment (MoCA) [ 36 ], a more challenging cognitive test compared to the MMSE, which includes executive function, higher-level language, and complex visuospatial processing, and is designed to detect milder impairments. In our previous investigation, we did not find a significant association between baseline SART performance and cognitive decline at 4 years as assessed by MMSE score [ 7 ], although SART performance and MMSE score offer two different measures of the same physiological system. Therefore, it was necessary to employ a different technique, which could allow to a higher specificity and detection of a small number of participants with signs of both physical and cognitive decline.…”
Section: Introductionmentioning
confidence: 88%
“…High IIV has been shown to be strongly correlated with inefficient sustained cognitive processes. Moreover, recent studies [ 4 , 7 ] have demonstrated that the use of the entire raw dataset could help clinicians find important features and peculiar associations that are otherwise hidden in derived measures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations